2018
DOI: 10.1590/1808-1657000232017
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus group: genetic aspects related to food safety and dairy processing

Abstract: Bacillus cereus group includes not pathogenic and high pathogenic species. They are considered as a risk to public health due to foodborne diseases and as an important cause of economic losses to industries due to production of spoilage enzymes. Some researches have been performed in order to assess the possible factors that contribute to put public health into risk because of consumption of food contaminated with viable cells or toxins which have complex mechanisms of production. The control of these bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
9
0
2
Order By: Relevance
“…Moreover, CodY is also a key pleiotropic regulator involving the growth and survival of this bacteria in various settlements including soil, food, insect guts and the human body and it performs an essential function in regulating and timing the expression of virulence gene within the B. cereus group (Ehling-Schulz et al 2019). Furthermore, the flagellar protein FlhF is necessary for optimal virulence, possibly due to the effect on protein synthesis and excretion, as well as the ability of gastric mucosa to sustain bacterial cells and probably to preserve enterotoxins from intestinal decay (Rossi et al 2018). The majority of B. cereus virulent factors belong to the PlcR, triggered during beginning of the stationary period by a small guiding peptide (PapR) being a quorum-sensing agent regulating the expression of many B. cereus toxins such as Nhe, Hbl, CytK, hlyI, SMas and PC-PLC, that may lead to the diarrhea by rupturing the epithelium (Fedhila et al 2006;Guillemet et al 2009;Tran et al 2010;Ceuppens et al 2011;Ehling-Schulz et al 2019).…”
Section: Pathogenesismentioning
confidence: 99%
“…Moreover, CodY is also a key pleiotropic regulator involving the growth and survival of this bacteria in various settlements including soil, food, insect guts and the human body and it performs an essential function in regulating and timing the expression of virulence gene within the B. cereus group (Ehling-Schulz et al 2019). Furthermore, the flagellar protein FlhF is necessary for optimal virulence, possibly due to the effect on protein synthesis and excretion, as well as the ability of gastric mucosa to sustain bacterial cells and probably to preserve enterotoxins from intestinal decay (Rossi et al 2018). The majority of B. cereus virulent factors belong to the PlcR, triggered during beginning of the stationary period by a small guiding peptide (PapR) being a quorum-sensing agent regulating the expression of many B. cereus toxins such as Nhe, Hbl, CytK, hlyI, SMas and PC-PLC, that may lead to the diarrhea by rupturing the epithelium (Fedhila et al 2006;Guillemet et al 2009;Tran et al 2010;Ceuppens et al 2011;Ehling-Schulz et al 2019).…”
Section: Pathogenesismentioning
confidence: 99%
“…é um patógeno de transmissão alimentar (9), sendo também reconhecido como o maior gênero de envolvimento em infecções nasocomiais (10). Já para o gênero Bacillus, há o grupo Bacillus cereus, composto por diversas espécies incluindo aquelas associadas a intoxicações alimentares (11). Tanto Bacillus spp., como Clostridium spp., também destacado nos resultados deste estudo, são bacilos gram positivos esporulados, termorresistentes.…”
Section: Discussionunclassified
“…cereus has been frequently reported as a major contaminant related to food spoilage. Many studies have isolated and identified B. cereus from diverse spoilt food products such as milk (Helmy, 1984;Dufrenne et al, 1995;Christiansson et al, 1999;Pacova et al, 2003;Valero et al, 2007;Bartoszewicz et al, 2008;Rossi et al, 2018;Ubong et al, 2020); egg products (Baron et al, 2007), and rice (Sarrías et al, 2002;Dierick et al, 2005;Haque and Russell, 2005;Rodrigo et al, 2021).…”
Section: Bacillus Cereus and Food Spoilagementioning
confidence: 99%